A VIRTUE-THEORETIC ANALYSIS OF OBJECTIVITY IN NEWS MEDIA - Sachdev, Kumar Neeraj (PEOPLE: International Journal of Social Sciences, 2019)
Journalists are professionals and their primary obligations are owed to business managers in their respective media firms, members of the public and society in general. These primary obligations lead to certain considerations and other associated obligations. One of the most important associated obligations for journalists is considered to be objectivity. That is to say, journalists have an obligation to report the news objectively and the media coverage ought not to be slanted in favor of government or any public or private agency. Alongside, journalists themselves are expected to be objective to report the news in a neutral manner. In view of this, I examine a few virtue-theoretic implications of objectivity in news media to argue for the need for journalists to cultivate the virtues of objectivity and care to overcome conflicting views and opinions in news media to report the news impartially even while sharing a bond of attachment with the people in the world.